EVALUATION OF PUYUH BUSINESS IMPACT IN KELURAHAN SIANTAN HILIR KECAMATAN PONTIANAK UTARA PONTIANAK CITY - Pondaw, Haidir (Jurnal Sains Pertanian Equator, 2019)
This study aims to determine the attitude of the community towards waste (odor and dust), the presence of flies caused by livestock business, and the contribution of quail livestock business to the people around the quail, Siantan Hilir Village, North Pontianak Subdistrict, precisely at Budi Utomo Street, Taman Anggrek Complex. The duration of the study is 30 days, namely on December 17, 2018 until January 17, 2019. This type of research is survey research. The data sources used are primary data obtained from giving questionnaires, and secondary data obtained from agencies related to this study. Data collection techniques using questionnaires, interviews, and observations. Data analysis used is descriptive statistical analysis, using a grouping model, simplification, and presentation such as frequency distribution tables and measurements using a Likert scale. The sample determined on the Slovin formula sample size amounted to 42 respondents. Variables of community attitudes with sub-variables of this observation are Waste, Smell, Flies, and Contributions. The overall results of the community's assessment of odor (85%), flies (81%), and waste (83%) showed very agreeable indicators which meant that people were very disturbed by the existence of quail livestock business in community settlements. While the community's assessment of contribution (36%) shows an indicator of disagreement which means that quail livestock business does not contribute to the surrounding community. Keywords: Odor, Flies, Waste, and Contributions.